The black box of governmental learning : the learning spiral -- a concept to organize learning in governments - Blindenbacher, Raoul (World Bank e-Library., 2010)
There are more poor people around the world than ever before. One of the missing factors in efforts to address poverty and increase sustainable development is adequate governmental capacity development. One effective means to improve the quality of democratic governance is by learning from the past and from others' experiences. The Black Box of Governmental Learning introduces the Learning Spiral--a new concept for organizing effective learning events for governments in the 21st century. It helps governments to learn from each other. This theory-based concept has been applied successfully over the past decade in numerous conferences, training, and e-learning events all over the world. The book is directed toward practitioners in governments, such as members of cabinets, parliaments, and courts; civil servants and politicians; civil society organizations; and international organizations. It will help them understand the challenges of learning in governments and offers a concept for organizing effective learning events.